Black on both sides : a racial history of trans identity - Snorton, C. Riley (University of Minnesota Press, 2017)
The story of Christine Jorgensen, America's first prominent transsexual, famously narrated trans embodiment in the postwar era. Her celebrity, however, has obscured other mid-century trans narratives - ones lived by African Americans such as Lucy Hicks Anderson and James McHarris. Their erasure from trans history masks the profound ways race has figured prominently in the construction and representation of transgender subjects. In this book, the author identifies multiple intersections between Blackness and transness from the mid-nineteenth century to present-day anti-Black and anti-trans legislation and violence. Drawing on a deep and varied archive of materials - early sexological texts, fugitive slave narratives, Afro-modernist literature, sensationalist journalism, Hollywood films - the author attends to how slavery and the production of racialized gender provided the foundations for an understanding of gender as mutable. In tracing the twinned genealogies of Blackness and transness, this book follows multiple trajectories, from the medical experiments conducted on enslaved Black women by J. Marion Sims, the 'father of American gynecology, ' to the negation of Blackness that makes transnormativity possible. Revealing instances of personal sovereignty among Blacks living in the antebellum North that were mapped in terms of 'cross dressing' and canonical Black literary works that express Black men's access to the "female within," this book concludes with a reading of the fate of Phillip DeVine, who was murdered alongside Brandon Teena in 1993, a fact omitted from the film Boys Don't Cry out of narrative convenience. Reconstructing these theoretical and historical trajectories furthers our imaginative capacities to conceive more livable Black and trans worlds. -- Provided by publisher